Digital Microwatershed Atlas-A tool for Watershed Development Planning - M.S.Selvi,; S.N.Das,; Shialendra Kumar,; Darshan Singh,; A.K.Yadav,; Munish Kumar,; S.K.Saha,; P.Laghate,; R.K.Sharma,; R.L.Meena, (Journal of Soil and Water Conservation, 2022)
Watershed development programme is one of the major initiatives of the country towards conservation of soil and water resources in the rainfed area to enhance agricultural production and to ensure livelihood security to rural people besides eco-development. Such endeavor needs scientific data base for evolving suitable strategy for planning purposes.Planning with conventional data base often becomes difficult by virtue of time required for collecting and collating data especially when it is to be dealt with spatial data. The modern tools in acquiring and managing natural resource data have revolutionized these fields that help in creation of digital data base leading a tremendous boost to the planning process.Soil and Land Use Survey of India (SLUSI) has set up necessary infrastructure for development to digital spatial data base for watersheds, soil and land characteristics for watershed development programme in the country. The paper deals with such an Endeavour to facilitate watershed development planning using digital base. It will help the planners to look at the status of soil and land resource at district level through various perspectives for conservation of natural resources through watershed development, agriculture development, restoring fragile eco-system besides generation of rural employment.